2024
DOI: 10.1111/sms.14651
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in 3‐ to 5‐year‐old children's motor competence: A pooled cross‐sectional analysis of 6241 children

Clarice Martins,
Elizabeth K. Webster,
Vicente Romo‐Perez
et al.

Abstract: There is some, albeit inconsistent, evidence supporting sex differences in preschoolers' motor competence (MC), with these observations not uniform when analyzed by age, and cultural groups. Thus, this study examined sex differences across ages in 3‐ to 5‐year‐old children's MC. A cross‐country pooled sample of 6241 children aged 3–5 years (49.6% girls) was assessed for MC using the Test of Gross Motor Development—2nd/3rd edition, and children were categorized into groups of age in months. Multiple linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This was similar to Hardy et al [31], in a study with 425 preschool children in Sydney, where boys performed better in object control and girls performed better in locomotion skills. This situation coincides with the above in a study by Martins et al [58] who, when evaluating the motor development of 6241 Brazilian children aged 3 to 5 years, concluded that girls presented better performance in locomotion tests mainly between 57 and 59 months, as well as at 66 and 68 months. Boys outperformed girls in ball skills tests in all age groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was similar to Hardy et al [31], in a study with 425 preschool children in Sydney, where boys performed better in object control and girls performed better in locomotion skills. This situation coincides with the above in a study by Martins et al [58] who, when evaluating the motor development of 6241 Brazilian children aged 3 to 5 years, concluded that girls presented better performance in locomotion tests mainly between 57 and 59 months, as well as at 66 and 68 months. Boys outperformed girls in ball skills tests in all age groups.…”
Section: Discussionsupporting
confidence: 91%
“…This coincides with the results presented by the authors of [ 35 ], in an intervention study to improve motor development, which showed that 93% of the children evaluated had a lower level of motor development than the chronological age. However, there is evidence that indicates that the higher the chronological age, the higher the motor age, a situation that is explained by the fact that as motor performance increases [ 60 ], there is also a greater maturation of the central nervous system [ 58 , 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%